Effect of fruit intake on functional constipation: A systematic review and meta-analysis of randomized and crossover studies - Huo, Jinghong; Wu, Lingyu; Lv, Jinming; Cao, Hongdou; Gao, Qinghan (Frontiers in Nutrition, 2022)
Functional constipation (FC) is commonly treated with fruits whose efficacy remain unclear. We conducted a meta-analysis of fruit intervention for FC and provided evidence-based recommendations. We searched seven databases from inception to April 2022. All randomized and crossover studies of the effectiveness of fruits on the FC were included. We conducted sensitivity and subgroup analysis. A total of 11 studies were included in this review at last. Four trials showed that kiwifruits have significantly increased the stool frequency (MD=0.26, 95% CI (0.22, 0.30), P＜0.0001, I2=0%) than palm date or orange juice in the fixed-effect meta-analysis. Three high-quality studies suggested that kiwifruits have better effect than ficus carica paste on the symptom of the FC assessed by the Bristol stool scale in the fixed-effect meta-analysis (MD=0.39, 95% CI (0.11, 0.66), P＜0.05, I2=27%). Besides, five trials showed that fruits can increase the Lactobacillus acidophilus (MD=0.82, 95% CI (0.25, 1.39), P＜0.05, I2= 52%) analysed with random-effect model. Subgroup meta-analysis according to the types of fruits suggested that fruits including pome fruit, citrus fruit and berries have increased the Bifidobacterium than the stone fruits in the random effect meta-analysis (MD=0.51, 95% CI (0.23, 0.79), P ＜ 0.05, I2=84%). Totally, fruits intake may have potential symptom alleviation on the FC as evidence shows they can affect stool consistency, stool frequency and gut microbiota. Further large-scale studies in clinic are needed to gain more confident conclusions concerning the association between fruits intake and FC.